2020
DOI: 10.1038/s42003-020-1093-z
|View full text |Cite
|
Sign up to set email alerts
|

Tract-specific analysis improves sensitivity of spinal cord diffusion MRI to cross-sectional and longitudinal changes in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a late-onset fatal neurodegenerative disease that causes progressive degeneration of motor neurons in the brain and the spinal cord. Corticospinal tract degeneration is a defining feature of ALS. However, there have been very few longitudinal, controlled studies assessing diffusion MRI (dMRI) metrics in different fiber tracts along the spinal cord in general or the corticospinal tract in particular. Here we demonstrate that a tract-specific analysis, with segmentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 32 publications
7
32
0
Order By: Relevance
“…A similar observation was recognized in longitudinal spinal cord DTI analyses in ALS, where authors found longitudinal changes only in more inferior spinal levels, suggesting, therefore, a dying-forward mechanism. 19 Our findings also correlate with the late presentation of upper motor neuron signs (such as weakness and spasticity) in FRDA patients. Nevertheless, it is important to highlight that our findings were limited to a cross-sectional analysis and further longitudinal studies are required to confirm these hypotheses, as well as to evaluate whether these results are reproducible and applicable to other segments of the spinal cord.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar observation was recognized in longitudinal spinal cord DTI analyses in ALS, where authors found longitudinal changes only in more inferior spinal levels, suggesting, therefore, a dying-forward mechanism. 19 Our findings also correlate with the late presentation of upper motor neuron signs (such as weakness and spasticity) in FRDA patients. Nevertheless, it is important to highlight that our findings were limited to a cross-sectional analysis and further longitudinal studies are required to confirm these hypotheses, as well as to evaluate whether these results are reproducible and applicable to other segments of the spinal cord.…”
Section: Discussionsupporting
confidence: 75%
“…Recently, specific DTI protocols for the spinal cord were developed and proved sensitive to detect abnormalities in several conditions, such as adrenoleukodystrophy, 11,12 Hirayama disease, 13 amyotrophic lateral sclerosis (ALS), 14,15 multiple sclerosis 16,17 as well as traumatic and non‐traumatic spinal cord injury 18 . Additionally, analysis of individual fiber tracts, referred to as tract‐specific DTI analysis, has been used to increase the sensitivity of spinal cord imaging to capture longitudinal changes in conditions such as ALS 19 …”
mentioning
confidence: 99%
“…From these pairs the susceptibility-induced off-resonance field was estimated and corrected using a method similar to that described in 37 . Subject motion and eddy-current induced distortions were corrected 38 as previously reported 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) models diffusion MRI data by assuming Gaussian diffusion at each location of the imaged tissue. Diffusion MRI of the spinal cord is challenging and has only recently received growing attention and seen new developments in the neuroimaging community 20-26 , with applications in disorders such as degenerative cord compression 27 , multiple sclerosis 28 , amyotrophic lateral sclerosis 23 and traumatic spinal cord injury 29 . To the best of our knowledge, only one study has reported cross-sectional data using dMRI in the spinal cord in FRDA 30 , and no longitudinal dMRI data have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Although C3–C6 WM or GM ROIs are quite large and coarse, it is feasible to proceed to finer analysis of tract-specific dMRI metrics utilizing a template and tract-specific atlas co-registration 37 , 40 . Tract-specific changes within our studied group of patients might be investigated, as demonstrated in the case of DCM 41 43 or ALS 44 patients.…”
Section: Resultsmentioning
confidence: 99%